Tennessee Women : Their Lives and Times - Wilkerson-Freeman, Sarah, 1956-; Bond, Beverly G. (Book collections on Project MUSE., 2015)
The second volume of Tennessee Women: Their Lives and Times contains sixteen essays on Tennessee women in the forefront of the political, economic, and cultural history of the state and assesses the national and sometimes international scope of their influence. The essays examine women's lives in the broad sweep of nineteenth- and twentieth-century history in Tennessee and reenvision the state's past by placing them at the center of the historical stage and examining their experiences in relation to significant events. Together, volumes 1 and 2 cover women's activities from the early 1700s to the late 1900s. Volume 2 looks at antebellum issues of gender, race, and class; the impact of the Civil War on women's lives; parades and public celebrations as venues for displaying and challenging gender ideals; female activism on racial and gender issues; the impact of state legislation on marital rights; and the place of women in particular religious organizations. Together these essays reorient our views of women as agents of change in Tennessee history.